1988
DOI: 10.1128/mcb.8.3.1352-1360.1988
|View full text |Cite
|
Sign up to set email alerts
|

Alternate trans Splicing in Trypanosoma equiperdum: Implications for Splice Site Selection

Abstract: We examined the structures of the 5' ends of mRNAs encoding variant surface glycoprotein 78 (VSG-78) and VSG-1(78) in Trypanosoma equiperdum. Several mRNA species were found for each gene, and all contained the 35-base miniexon (or spliced leader) sequence attached at different positions on their 5' ends. Thus, the generation of multiple messages for each VSG occurred by attachment of the miniexon at one of several 3' splice acceptor sites. The frequency with which individual splice sites were used varied from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The two 2.3-kb cDNAs analyzed do not start exactly at the same position, but both are capped with a miniexon sequence. That the miniexon can be added at several possible locations of the same sequence has already been shown by Layden and Eisen (13). On the basis of the observations by these authors, the 3' splice sites transcript (Cl and C2) were determined and found to be identical to the corresponding one from the expression site (ESAG 6 and 0.7 kb of upstream region).…”
Section: Resultsmentioning
confidence: 65%
“…The two 2.3-kb cDNAs analyzed do not start exactly at the same position, but both are capped with a miniexon sequence. That the miniexon can be added at several possible locations of the same sequence has already been shown by Layden and Eisen (13). On the basis of the observations by these authors, the 3' splice sites transcript (Cl and C2) were determined and found to be identical to the corresponding one from the expression site (ESAG 6 and 0.7 kb of upstream region).…”
Section: Resultsmentioning
confidence: 65%